Are discourse comprehension and cognitive processes influenced by the type of language language (English and Spanish)? A cross-language study based on elaborative inferences generation - Escudero Domínguez, Inmaculada; León, José A.; Morera, Yurena (Revista de Investigación Educativa, 2012)
The aim of this study was to determine whether discourse comprehension processes, focusing on the type of inferences activated during reading, would be influenced by the language (English and Spanish) as supported by linguistic relativity theories. 20 U.S. and 20 Spanish undergraduates took part in this study using a think-aloud task. The results suggest that inference generation was not restricted by language differences. In contrast, these data support the idea that inference activation reflects a universal cognitive processes pattern